A new xanthone from Garcinia nitida - Awang, K.; Ee, G.C.L.; Foo, C.H.; Jong, V.Y.M.; Ismail, N.H.; Sukari, M.A.; Taufiq Yap, Y.H. (Taylor & Francis, 2012)
A detailed chemical study on the stem bark of Garcinia nitida has led to the isolation of five xanthones. They are 1,6-dihydroxy-5-methoxy-6,6-dimethylpyranol[2',3':2,3]-xanthone(1),inophyllin B (2), osajaxanthone (3), 3-isomangostin(4 ) and rubraxanthone (5). The structures of these compounds were established using mainly l-D and 2-D NMR spectroscopy(¹H,¹³C, DEPT,COSY, HMBC and HMQC) while molecular masses were determined via MS techniques;1 is a new compound.